Combating plagiarism : a hands-on guide for librarians, teachers, and students - Darr, Terry (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2019)
"Offers an instructional plan for plagiarism education for middle school and high school students, allowing librarians to become a resource for students, teachers, and school administrators"--